Elevated cystatin C: is it a reflection for kidney or liver impairment in hepatic children? - El-Sayed, Behairy; El-Araby, Hanaa; Adawy, Nermin; Hassona, Mona; El-Nady, Naglaa; Zakaria, Haidy; Khedr, Mohammed (Clinical and Experimental Hepatology, 2017)
Aim of the study : To assess if elevated serum cystatin C (Cyst-C) is an indicator for renal or hepatic dysfunction in presence of liver fibrosis. Material and methods : Data of 50 children with chronic liver diseases (CLDs), out of which 25 were without renal impairment, and 25 with renal impairment were analyzed. Twenty healthy children served as a healthy control group. Routine investigations, creatinine clearance, hepatitis viral markers, abdominal ultrasonography, and liver biopsy were performed for patients with CLDs. Measurement of serum Cyst-C concentration by particle induced immunonephelometry were completed for both patients and control group. Results : Results showed that serum Cyst-C is not correlated with the degree of hepatic impairment (p > 0.05). Cyst-C levels were significantly higher in patients with renal impairment (3.66 ± 0.85) than those without (0.71 ± 0.12), and healthy control group (0.63 ± 0.85). Cystatin-C showed significant elevation in patients with severe fibrosis with renal impairment (3.66 ± 0.85) than those without (0.76 ± 0.04) (p 2.34 mg/l predicting GFR 2.73 mg/l predicting GFR < 20 ml/min with accuracy of 81.5%. Conclusions : Serum Cyst-C is a promising marker to estimate renal impairment in children with CLDs. Further studies are needed to estimate the accuracy of serum Cyst-C for early detection of renal impairment and close monitoring of the hepatic children.